The effectiveness of the implementation of collaborative writing and students’ perception on the strategy - Lau, Kai Yee (2023)
This study was conducted to explore the effectiveness of implementing collaborative writing into students’ writing skills and investigate students’ perceptions of collaborative writing. Twenty-five Form 3 students from SMK Malim Nawar, Kampar, were involved in this study. This study utilised quasi-experimental design, where pre-test and post-test will be given to students. The researcher also conducted a semi-structured interview to achieve the second objective of the research. The results obtained from the pre-test and post-test indicated that collaborative writing had a positive effect on ESL secondary school students’ writing skills. Furthermore, the results of interview showed that most students held a positive attitude towards collaborative writing.